Congress volume : Leiden, 2004 - Lemaire, André, 1942- (Supplements to Vetus Testamentum,, 2006)
This volume presents all the main lectures of the XVIIIth Congress of the International Organization for the Study of the Old Testament (IOSOT) held in Leiden (August 2004). It is a very good sample of the main trends and progress of current biblical research on textual criticism (Qumran and Septuagint), biblical archaeology, literary criticism (especially Pentateuch, Joshua, Kings), biblical themes (especially in wisdom literature), as well as about the light thrown on biblical exegesis by current cognitive linguistics. An appendix deals with the connection between world Christianity and the study of the Old Testament. The twenty authors are among the main international figures of current biblical exegesis and their contributions are representative of the study of the Old Testament at the beginning of the third millenium.